The Effect of Price Discount on Impulse Buying Behavior (Study on E-Commerce Sociolla) - Nadia Salsafira; Nurvita Trianasari (Budapest International Research and Critics University, 2022)
Internet use in 2021 is as many as 202.6 million people due to activities switching to using the internet. In terms of work, education, and personal needs using the internet, thus providing an opportunity for entrepreneurs to carry out buying and selling activities using electronic media or e-commerce. For consumers, e-commerce makes it easy for them to fulfill their needs, one of which is the purchase of cosmetics. Sociolla is a beauty e-commerce that sells several beauty products by giving a number of discounts so as to give consumers positive energy to buy beauty products impulsively or suddenly. This study aims to determine the effect of price discount on impulse buying behavior in Sociolla e-commerce. This study uses a quantitative method with an individual unit of analysis for Sociolla e-commerce users in Jakarta with a productive age range of 15-64 years. The number of samples used in this study were 400 respondents with the sample method used was non-probability sampling and used purposive sampling. The analysis technique used is simple linear regression analysis. Data collection for this study was conducted through an online questionnaire distributed to individual Sociolla e-commerce users in Jakarta with a productive age range of 15-64 years.